Desvendando a riqueza financeira: Fluxos e estoques financeiros no Brasil - Antonio Carlos Macedo e Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper deals with the financial wealth. It shows, firstly, how it was inserted into the Systems of National Accounts recommended by multilateral institutions, and, in particular, how it is treated by the most recent version of the system (2008). After that, it discusses the evolution and the current state of the so-called integrated macroeconomic accounts in Brazil, showing both the improvements and limitations. Finally, it tries to extract some stylized facts about the dynamics and structure of the financial wealth in Brazil, using the financial accounts (2005-2009), the balance sheet accounts (2004-2009) and the 2009 balance sheet matrix.
Keywords: E16; E44; 330; social accounting matrix; flow of funds; financial wealth